How important are financial frictions in the US and the Euro area - Virginia Queijo von Heideken (Sveriges Riksbank, 2008)
This paper aims to evaluate if frictions in credit markets are important for business cycles in the U.S. and the Euro area. For this purpose, I modify the DSGE financial accelerator model developed by Bernanke, Gertler and Gilchrist (1999) by adding frictions such as price indexation to past inflation, sticky wages, consumption habits and variable capital utilization. When I estimate the model with Bayesian methods, I find that financial frictions are relevant in both areas. According to the posterior odds ratio, the data clearly favors the model with financial frictions both in the U.S. and the Euro area. Moreover, consistent with common perceptions, financial frictions are larger in the Euro area.
Keywords: C11; C15; E32; E40; E50; G10; 330; Financial frictions; DSGE models; Bayesian estimation; Konjunkturtheorie; Liquiditätsbeschränkung; Dynamisches Gleichgewicht; Bayes-Statistik; Eurozone; EU-Staaten; USA